ASHRAE greenguide : the design, construction, and operation of sustainable buildings. (American Society of Heating, Refrigerating, and Air-conditioning Engineers, 2006)
"The ASHRAE GreenGuide was developed primarily to provide guidance to designers of HVAC & R systems in how to participate effectively on design teams charged with producing green buildings"--Provided by publisher
Keywords: Sustainable buildings -- Design and construction.; Sustainable architecture.; Buildings -- Environmental engineering.; elektronické knihy; electronic books